Legalidad y prescripción frente a la investigación de crímenes de lesa humanidad en Colombia (2013)
This article analyzes the tension existing between the principle of legality and thestatute of limitation of the criminal action in Colombia, and the duty to investigateand prosecute crimes against humanity under international law.